The Impact of Verbal Violence that the Family Members are Making on Children's Social Emotional Aspects: A Case Study In Early Age 2-4 Years - Wahyuni, Hendra (International Journal for Educational and Vocational Studies, 2020)
The study aims to know the impact of violence verbal carried members of the family of the aspects of social, emotional children aged early 2-4. With the approach to study the case with methods of qualitative found that violent verbal in children aged early majority do mothers with an age, angry exaggeration, understatement, compare and threats. The cause of mother doing verbal among them: a factor of economic, educational, rage against the couple as well as how to view the parents, of the child and factors environment. Impacts on children's emotional, social aspects: a) intensity of violence around, imitated by children and difficult to be dammed by parents, b) always must be number one, c) instructive, d) aggressive and sensitive, e) challenging to succumb to, f) dependence on high mother. When members of the family often yell, children also perform on other people even dare to yell at people of his own as well as the loss of independence and a sense of trust themselves children. So, the level of emotional, social maturity of family members is very influential in the development of emotional, social aspects of children of age religious.